Persepsi Masyarakat terhadap Keberadaan Peternak Ayam Broiler di Kelurahan Rijang Pitu Kecamatan Maritengngae Kabupaten Sidenreng Rappang - Iksan, M; Nugraha, A; Armayani, A (Politeknik Negeri Lampung, 2024)
The aim of this research is to find out how the residents of Rijang Pitu sub-district, Maritengngae District, and Sidenreng Rappang Regency perceive the existence of broiler chickens. The research was conducted from July 29 to September 29 2023 at Rijang Pitu Village, Maritengngae District, Sidenreng Rappang Regency. sample used in this research were people who lived close to broiler chicken breeders with a total of 38 respondents. Samples were taken using purposive sampling. The type of study carried out in this research is descriptive and quantitative with a Likert scale. To measure the subvariables odor, fly population, and livestock waste, the measurement scale is very disturbed, disturbed, quite disturbed, not disturbed, and very not disturbed. The results of the research show that the odor generated from livestock is in the moderately disturbed category with a weight value of 374, the fly population generated from livestock is in the disturbed category with a weight value of 392, and the waste generated from livestock is in the moderately disturbed category with a weight value of 366. It can be concluded that the perception of society as a whole is in the moderately disturbed category with an overall weight of 1.132.